Association of common promoter polymorphisms of MCP1 with hepatitis B virus clearance - Park, Byung Lae; Kim, Yoon Jun; Cheong, Hyun Sub; Kim, Lyoung Hyo; Choi, Yoo Hyun; Lee, Hyo-Suk; Shin, Hyoung Doo (Experimental & molecular medicine, 2006)
Hepatocellular carcinoma (HCC) is one of the most common malignant cancers closely associated with chronic infection by the hepatitis B virus (HBV) or the hepatitis C virus (HCV) throughout the world. In this study, the genetic associations of 20 known polymorphisms in eight candidate genes, including angiotensinogen (AGT), cadherin 1 (CDH1), cyclooxygenase 2 (COX2), monocyte chemotactic protein-1 (MCP1), multidrug resistance 1 (MDR1), chemokine ligand 5 (RANTES), thrombospondin 2 (THBS2), and thrombospondin 4 (THBS4), were analyzed in a large chronic hepatitis B cohort (n=1,095) recruited from the Korean population. In addition, three polymorphisms in chemokine receptor 4 (CXCR4) and vimentin (VIM) identified in this study were also genotyped. Using logistic regression analysis controlling possible confounding factors, one common (freq.=0.367) promoter polymorphism of MCP1 (MCP1-2518G>A) among analyzed polymorphisms was significantly associated with clearance of HBV infection. The frequency of homozygotes for the MCP1-2518A allele (MCP1-2518A/A) among chronic hepatitis B virus (HBV) carrier patients was significantly higher than that among spontaneously recovered (SR) subjects (17.7% vs. 10.4%)(OR=1.78, P=0.004). Our findings imply a plausible explanation for the contribution of host genetic determinants to the variable outcome of HBV infection, which might provide valuable information for future genetic study in this area.